PTU-032 Alcohol use disorders and liver fibrosis-can we improve the referral pathway to secondary care?. (June 2019) - Rhodes, Freya; Cococcia, Sara; Patel, Preya; Connoley, Declan; Rosenberg, William
Abstract : Introduction: Alcohol is the leading cause of cirrhosis in the UK, which often presents late when patients have already decompensated. Mortality from cirrhosis has increased 400% since 1970. There is therefore an urgent need for earlier detection of advanced fibrosis in primary care (PC), so that interventions can be implemented to improve outcomes. Detecting fibrosis/cirrhosis in PC is challenging as patients are often asymptomatic. There is increasing interest in the use of non-invasive tests (NIT) for liver fibrosis. We aimed to review referrals from PC to hepatology clinic for patients with alcohol use disorders (AUD), and evaluate the proportion of these patients that had evidence of advanced fibrosis. Methods: 1, 657 new GP referrals to hepatology clinic at the Royal Free Hospital from Jan 2015-Jan 2017 were reviewed, and those with suspected alcohol-related liver disease (ALD) as reason for referral were selected and analysed. Data were collated on demographics, fibrosis staging, reason for referral and alcohol use. Results: 141 patients were referred with suspected ALD (71% male, median alcohol intake 70 units/week) (IQR 49–140). Most patients (64%, 90/141) were referred on the basis of abnormal liver function tests (LFTs), alcohol history, steatosis on ultrasound (US), or examination findings. Of those referred 24.8% (35/141) had US findings of chronic liver disease prior to referral. Of these, 34% (12/35) were subsequently deemed not to have advanced fibrosis or cirrhosis in secondary care. Prior to referral, 89% (125/141) of patients had not had a NIT for liver fibrosis. Once seen by hepatology, only 36.2% of the referred patients (51/141) were confirmed to have either advanced fibrosis or cirrhosis (by fibroscan, imaging, biopsy or ELF), and were kept under follow up. The remaining 63.8% were discharged back to PC and represent unnecessary referrals that may have been avoided through the use of NIT in primary care. Current BSG guidance does not recommend routine NIT in patients with AUD drinking <35/50 units/week(F/M) with AUDIT score <19 but in this review of patients referred from PC a diagnosis of advanced fibrosis or cirrhosis was confirmed in 3/23 of male patients drinking 14–49 units/week. Conclusions: We propose that the use of NIT in PC patients with AUD would significantly reduce the number of 'unnecessary' referrals to secondary care, and increase the earlier detection of advanced fibrosis. US cannot always be relied on for a diagnosis of cirrhosis. Further research is needed to determine which thresholds of alcohol intake warrant application of NIT, and it would be interesting to repeat this study in 2020 to evaluate the impact of the 2017 BSG LFT guidelines.